2018
DOI: 10.15611/eada.2018.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality of households in Poland: A subgroup decomposition of generalized entropy measures

Abstract: A formula of measures applied to assess the level of income inequality results from the intellectual basis on which this approach is founded. Our paper focuses on Generalized Entropy measures. The aim of our paper is twofold. Firstly, it aims at presenting GE measures and discussing their properties, especially the property of additive decomposition. Secondly, the empirical aim is to assess the level of income inequality in Poland and to indicate its main determinants. In the study we use microdata obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
(30 reference statements)
4
10
1
Order By: Relevance
“…This was also true in our study, as malnutrition and food insecurity was also more prevalent among rural children belonging to the lowest socioeconomic class. Decomposed results of this study showed within group income variations to be a strong indicators of explaining socioeconomic inequalities, the latter findings also concur with results of the Poland study [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was also true in our study, as malnutrition and food insecurity was also more prevalent among rural children belonging to the lowest socioeconomic class. Decomposed results of this study showed within group income variations to be a strong indicators of explaining socioeconomic inequalities, the latter findings also concur with results of the Poland study [31].…”
Section: Discussionsupporting
confidence: 89%
“…The study focused on two household characteristics in assessing income inequalities thus; location of the household and socioeconomic status. Economic inequalities among regions and socioeconomic classes within a country may can be attributed as the driving force of income inequalities as uneven progress in development across regions can result in the diversification of income and worsening income of inequalities [31].…”
Section: Decomposition By Residencementioning
confidence: 99%
“…Decomposed results of this study showed within group household wealth variations to be strong indicators explaining socioeconomic inequalities, the latter ndings also concur with results of other studies [15,54]. More recently, a study used Shapley decomposition to estimate the relative contributions of circumstances and analysed patterns of inequalities in health relative to nutrition outcomes among children under ve in Tunisia [19].…”
Section: Discussionsupporting
confidence: 88%
“…The study focused on two household characteristics in assessing health inequalities: location of the household and socioeconomic status/class. Socioeconomic inequalities among regions and socioeconomic classes within a country can be attributed as the driving force inducing uneven progress of economic development across regions [54].…”
Section: Decomposition Analysismentioning
confidence: 99%
“…Today, entropy is part of the methodological output of world geography and application in many and varied research field studies (Batty, , , ; Wilson, ). In Poland, an upsurge of interest in the entropy method can be observed in spatial econometrics (Muszynska & Wędrowska, ). In Polish socioeconomic geography, the latest works on the use of entropy include a study of changes in the land‐use pattern in metropolitan areas (Werner et al., ) and an analysis of the convergence of regional development (Kudrycka, ).…”
Section: Uncertainty Measurement In Economic Disparitymentioning
confidence: 99%